Empirical analysis and evaluation of the determinants of credit risk of the EU banking system - FANG, ZHENG (2019)
Credit risk is one of the most important types of risk for banks, which could be measured by non-performing loans. This dissertation aims to analyses and evaluates the determinants of the credit risk of the EU banking system from 2012 to 2017. The dissertation uses the method of panel data, and the data comes from the database such as the Orbis Global database. The empirical analysis results show that, among the microeconomic variables, the loan loss provisions have a significant positive impact on credit risk. Among macroeconomic variables, the GDP growth rate and the unemployment rate have significant positive influences. When conducting risk regulation, the EU banking system can use these factors as early warning indicators for non-performing loans and take measures before credit risks occur.